Ypsolopha milfontensis Corley & Ferreira, a new species from the Portuguese coast (Lepidoptera: Ypsolophidae) - M. F. V. Corley; S. Ferreira (SHILAP)
Ypsolopha milfontensis Corley & Ferreira, sp. n. is described from the coast of south-west Portugal where its hostplant is Ephedra fragilis Desf. It is closely related to Ypsolopha instabilella (Mann, 1866), but with some differences externally, in male and female genitalia and a significant difference in DNA barcode.